2023
DOI: 10.1021/jacs.3c03581
|View full text |Cite
|
Sign up to set email alerts
|

α-Helix-Mediated Protein Adhesion

Abstract: Proteins have been adopted by natural living organisms to create robust bioadhesive materials, such as biofilms and amyloid plaques formed in microbes and barnacles. In these cases, β-sheet stacking is recognized as a key feature that is closely related to the interfacial adhesion of proteins. Herein, we challenge this well-known recognition by proposing an α-helix-mediated interfacial adhesion model for proteins. By using bovine serum albumin (BSA) as a model protein, it was discovered that the reduction of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Recently, a novel film material system was built through such amyloid-like aggregation of BSA, 64–66 providing new insight into protein interfacial adhesion. Previous studies on protein adhesion have identified β-sheet stacking as a key feature closely associated with the interfacial adhesion of proteins.…”
Section: Sli-mediated Biopolymer Assemblymentioning
confidence: 99%
“…Recently, a novel film material system was built through such amyloid-like aggregation of BSA, 64–66 providing new insight into protein interfacial adhesion. Previous studies on protein adhesion have identified β-sheet stacking as a key feature closely associated with the interfacial adhesion of proteins.…”
Section: Sli-mediated Biopolymer Assemblymentioning
confidence: 99%
“…Likewise, in another instance, barnacles employ their cement to achieve firm adhesion to reef or boat surfaces, employing a composition primarily dominated by amyloid-like components rich in b-sheet motifs. 98 In contrast to earlier reports outlining the surface adhesion of proteins mediated by b-sheet stacking, Zhang and Yang et al 142 proposed an a-helix-mediated interfacial adhesion model of proteins (Fig. 6d).…”
Section: Adhesion Mechanisms Of Proteins To Interfacesmentioning
confidence: 81%
“…In addition, intermolecular disulfide crosslinking within the adsorption layer further contributed to this adhesion phenomenon. 142 In summary, protein adhesion to interfaces involves a nuanced interplay of adsorption, molecular recognition, conformational changes, thermodynamics, and desorption. Biochemists play a central role in unraveling these complex mechanisms and applying their knowledge to diverse applications while addressing the challenges posed by the multifaceted nature of protein–interface interactions.…”
Section: Artificial Strategies Of Protein-based Bioactive Coatings In...mentioning
confidence: 99%
“…For sample K L25 BE L25 , the α-helix content is 55% and the β-sheet content is 45%, whereas for sample K L25 BE D25 , the α-helix content is 30% and the β-sheet content is 70%. A higher α-helix content is correlated with a stronger adhesive strength, potentially attributed to the increased exposure of side groups at the polypeptide surface due to α-helical structure, providing enhanced interfacial adhesion with the substrate (Figure g) . Then the helical content of K L35 BE L15 and K L15 BE L35 was further calculated according to FT-IR spectra (Figure e and f).…”
mentioning
confidence: 99%
“…A higher α-helix content is correlated with a stronger adhesive strength, potentially attributed to the increased exposure of side groups at the polypeptide surface due to α-helical structure, providing enhanced interfacial adhesion with the substrate (Figure 3g). 53 Then the helical content of K L35 BE L15 and K L15 BE L35 was further calculated according to FT-IR spectra (Figure 3e and 3f). Among K L35 BE L15 , K L25 BE L25 , and K L15 BE L35 , the helical content increases with the increasing ratio of benzyl glutamate, which can be attributed to the high helical propensity of poly(benzyl glutamate) chains.…”
mentioning
confidence: 99%